Ultraviolet Upconversion Luminescence in a Highly Transparent Triply-Doped Gd3+-Tm3+-Yb3+ Fluoride-Phosphate Glasses - Galleani, Gustavo [UNESP]; Santagneli, Silvia Helena [UNESP]; Ledemi, Yannick; Messaddeq, Younès [UNESP]; Janka, Oliver; Pöttgen, Rainer; Eckert, Hellmut (American Chemical Society (ACS), 2018)
We report near-infrared to ultraviolet (UV) upconversion emissions in triply-doped Gd3+-Tm3+-Yb3+ fluoride-phosphate glasses. Emission at 310 nm, originated from the Gd3+:6P7/2 →8S7/2 transition, was observed for the first time in glasses. The high-purity glasses prepared exhibit extended transparency in the UV down to 200-250 nm. The mixed fluoride-phosphate environment of the rare-earth ions was characterized by means of NMR techniques using scandium as a diamagnetic mimic for the luminescent species, for which the ligand distribution was quantified by 45Sc{31P} rotational echo double-resonance NMR. Both the intensity of the Gd3+ emission as well as those of the UV emissions at 290, 347, and 363 nm increase with increasing ratio of fluoride to phosphate ligands coordinating to the rare-earth ion.